The Influence Of Product Quality, Price, And Brand Ambassador On Avoskin Product Purchase Decisions Through Purchase Intention As An Intervening Variable - Sari, Dian Puspita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the influence of Product Quality, Price, Brand Ambassador on Purchase Decisions with Buying Interest as an Intervening Variable (Case Study on Avoskin Product Users in East Semarang). The data collection method used in this study uses a survey by distributing questionnaires to respondents who have met the criteria. Then it was processed using SmartPLS version 3 with a total of 400 respondents. The latest in this study is that there is the addition of variables that are different from previous research and different research locations or places so that the results found are different. The results of this study show that product quality, price, and brand ambassadors affect buying interest. Product quality has no effect on the purchase decision, price and brand ambassador affect the purchase decision. The results of this study also show that buying interest has an effect on purchase decisions. In addition, buying interest can mediate between product quality, price, brand ambassador and purchase decision.